Metodiceskie podchody napravlennosti v razvitii silovych vozmožnostej lyžnikov-gonšcikov na etapach sportivnoj podgotovki - Reutskaya, E. A.; Pinyagin, P. Yu. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The increasing of power capabilities of skiers at the stages of long-term sports training has been investigated. With helping of the method of associative rules, we determined the relationships between the indicators of the speed-strength capabilities and power endurance of the muscles of the shoulder girdle with the effectiveness of competitive activity of skiers at the stages of sports training. We determine the vectors in the increasing of the power capabilities of skiers at the training stage and the stage of improving sports experience.